P079 Valproic acid increases MiR449a expression in intestinal mucosa from patients with inflammatory bowel disease. (27th May 2021) - Felice, C; Lewis, A; Armuzzi, A; Lindsay, J O; Silver, A
Abstract: Background: Histone acetylation/deacetylation and microRNAs (MiRNA) are epigenetic mechanisms involved in the pathogenesis of inflammatory bowel diseases (IBD). Histone deacetylase (HDAC) inhibitors, such as valproic acid (VPA), demonstrated anti-inflammatory and anti-tumour effects in animal models of colitis. 1, 2 Modulation of MiRNAs is hypothesized to be a possible mechanism of action of HDAC inhibition. 3 Recently, VPA was shown to modulate histone-3 (H3) acetylation and cytokine production in the human gut. 4 In this study, we analysed whether VPA influences MiRNA expression in ex-vivo biopsies from IBD patients. Methods: Colonic biopsies from IBD patients collected during routine endoscopic procedures were cultured with VPA (5 mM) or control media for 24 hours. Total RNA was extracted and a MiRNA array was performed (miScript™ miRNA PCR Array), profiling the expression of 84 MiRNAs predicted to regulate pro- or anti-inflammatory genes. Significantly altered MiRNAs were then validated in an independent cohort of samples using quantitative (q) RT-PCR. Caco-2 (ATCC ® HTB-37™) cell cultures treated with VPA (5 mM) or control media were used to confirm changes of H3 acetylation and MiRNA expression. After 24 hours, H3 acetylation was evaluated by immunofluorescence and apoptotic markers were analysed by qPCR. Results: Colonic biopsies from inflamed mucosa of 6 IBD patients (2 with Crohn's disease (CD) and 4 with ulcerative colitis (UC)) were cultured with VPA or control media. MiRNA analysis showed a significant increase of miR449a, miR373-3p, miR300 and miR520d-3p in treated biopsies compared to control (p=0.004, p=0.024, p=0.04 and p=0.014, respectively). Validation was performed in an independent cohort of 14 IBD patients (7 CD; 7 UC), confirming a significant increase of MiR449a (p=0.026) in VPA treated biopsies. VPA treated Caco-2 cell cultures showed a significant increase of H3 acetylation density level (p=0.02), confirming the HDAC inhibitory activity. Gene expression analysis showed increased Caspase-3 (p=0.015), a pro-apoptotic marker, and decreased BCL-3 (p<0.01), an anti-apoptotic marker. The level of MiR449a expression in VPA treated cells was significantly elevated (p<0.01). Conclusion: VPA increases the expression of MiR449a in cultured ex-vivo biopsies and in Caco-2 cells. This MiRNA has recently demonstrated to be involved in IBD pathogenesis and in colitis-associated colon cancer. This may represent a new insight into IBD pathogenesis and colitis-associated colon cancer development. Further work is required to determine the functional significance of miR-499a in the human intestine. References: Glauben R, et al. J Immunol 2006. Tanaka T. Cancers 2012. Abe F, et al. Oncotarget 2017. Felice C, et al. Cell Mol Gastroenterol Hepatol 2021.